Taxonomic and phylogenetic characterizations reveal four new species of Simplicillium (Cordycipitaceae, Hypocreales) from Guizhou, China - Wan-Hao Chen (Nature Portfolio, 2021)
Abstract Simplicillium species are commonly found from soil, seawater, rock surface, decayed wood, air and as symbiotic, endophytic, entomopathogenic and mycoparasitic fungi. Minority insect-associated species was reported. Simplicillium coccinellidae, S. hymenopterorum, S. neolepidopterorum and S. scarabaeoidea were introduced as the newly insect-associated species. The phylogenetic analyses of two combined datasets (LSU + RPB1 + TEF and SSU + ITS + LSU) revealed that S. coccinellidae and S. hymenopterorum were both nested in an independent clade. S. neolepidopterorum and S. scarabaeoidea have a close relationship with S. formicidae and S. lepidopterorum, respectively. S. neolepidopterorum can be easily distinguished from S. formicidae by ellipsoidal to cylindrical, solitary conidia which occasionally gather in short imbricate chains. S. scarabaeoidea could be easily distinguished from S. lepodopterorum by having longer phialides and larger conidia. Based on the morphological and phylogenetic conclusion, we determine the four newly generated isolates as new species of Simplicillium and a new combination is proposed in the genus Leptobacillium.